SUPPLY CHAIN OUTSOURCING: MANAGEMENT ACCOUNTING AND CONTROL SYSTEMS USED IN INTER-ORGANISATIONAL RELATIONSHIPS - Baciu, Andreea-Cristina (2016)
Inter-organisational relationships created through outsourcing have become popular in recent years. Researchers have shown increased interest in management accounting and control systems used in such relationships, however previous studies identify potential areas for future research. The purpose of this research is to build on previous studies and to identify what management accounting and control systems organisations implement when they enter into an inter-organisational relationship following an outsourcing decision, in order to mitigate potential risks and maintain control over the supplier’s performance and activities. The methodology chosen is a case study conducted in an IT company that outsourced part of its supply chain function to a third party logistics provider. Data were collected through semi-structured interviews conducted with members of the Supply Chain and Procurement Teams. Findings show that risks are mitigated through partner selection criteria, contractual agreements and frequent meetings. The supplier’s performance is controlled through performance measurement tools, integrated information systems and cost models. The implementation of these management accounting and control systems enabled the partners to achieve a collaborative relationship.